Spontaneous intracranial hypotension causing headache in a child: A case report and overview of CT myelogram technique - Rhea Taneja; Timothy K.Y. Lee; Manish Taneja (Interdisciplinary Neurosurgery, 2023)
Background: Spontaneous Intracranial Hypotension (SIH) is a well-known condition, generally presenting as a postural headache in individuals between the ages of 40 and 50 years. Cases within the paediatric population are rare, and may require deviation from the traditional pathways of diagnosis and treatment. Case presentation: We report the case of a 10-year-old girl who presented with the symptoms of intracranial hypotension. However, due to poor recognition of the disease within the paediatric population, diagnosis was not confirmed for over a year before tertiary help was sought. Conclusion: In this report we highlight the need for differential diagnosis of spontaneous intracranial hypotension in children, and propose the use of a combined approach involving CT myelography and targeted EBP as an effective management strategy for these patients.